Impact of Demographical Factors on Work Life Balance among Academic Staff of University of Kelaniya, Sri Lanka - Padmasiri, M.K.D.; Mahalekamge, W.G.S. (Journal of Education and Vocational Research, 2016)
The focus of this research is to find out the impact of demographical factors on Work Life Balance among academic staff of University of Kelaniya. Objective is examining the impact of selected demographical factors; gender, marital status and investigate best and worst gender level and marital status of Work Life Balance. Research sample consists with 150 lecturers out of 560 lecturers in University of Kelaniya. Based on random sampling method standardized questionnaires are distributed to collect data. Based on the analysis researchers identified that there is significant relationships among gender, and marital status and Work Life Balance excluding age as a demographic factor. Further identified females as a best group in Work Life Balance and under marital status single group is having Work life Balance greater than married group. Based on findings researchers established that there is a significant impact of gender and marital status on Work Life Balance as demographic factors.